Preparation method of efficient photocatalyst and method for enhancing Fenton flue gas denitration by using photocatalyst

By preparing high (001) crystalline titanium dioxide photocatalyst F-TiO2 and high-efficiency photocatalyst CoOx@F-TiO2, the problem of slow Fe(III)/Fe(II) circulation speed in Fenton flue gas denitrogenation was solved, significantly improving the denitrification efficiency and NO capture ability, and achieving efficient flue gas denitrogenation effect.

CN119500198AActive Publication Date: 2025-02-25EAST CHINA UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411669192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the prior art, the Fe(III)/Fe(II) cycle speed during the Fenton flue gas denitrogenation process is slow, resulting in low denitrification efficiency, and the catalytic capacity of the TiO2 photocatalyst is insufficient, which cannot meet the demand for photocatalytic wet method Fenton denitrification.

Method used

By preparing high (001) crystalline titanium dioxide photocatalyst F-TiO2 and high-efficiency photocatalyst CoOx@F-TiO2, crystalline surface engineering and selective photodeposition technology, the electron and hole separation efficiency of the photocatalyst is improved and its catalytic activity is enhanced.

Benefits of technology

The Fe(III)/Fe(II) circulation speed is significantly accelerated, the Fenton denitrification efficiency is improved, the NO capture capacity is enhanced, and efficient flue gas denitrification is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500198A_ABST
    Figure CN119500198A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-efficiency photocatalyst and a method for enhancing Fenton flue gas denitration by using the photocatalyst, and belongs to the technical field of photocatalysis-oxidation wet denitration. The preparation method comprises the following steps: firstly, taking tetrabutyl titanate as a Ti source, taking a hydrofluoric acid solution as a crystal face regulator, and carrying out solvothermal reaction to obtain F-TiO2 with a high (001) crystal face; and uniformly mixing sodium iodate serving as an electron sacrificial agent, cobalt salt serving as a Co precursor and the high (001) crystal face F-TiO2 serving as a carrier, and generating cobalt oxide which is selectively loaded on the high (001) crystal face titanium dioxide under the condition of ultraviolet light, thereby obtaining the CoOx-coated F-TiO2 photocatalyst. And the F-TiO2 photocatalyst and the CoOx coated F-TiO2 photocatalyst are used for flue gas Fenton denitration. The problem that excessive Fe (III) is accumulated in Fenton denitration is solved, iron circulation in the reaction is accelerated, and the denitration capacity of the Fenton reaction is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic-oxidative wet denitration, and in particular to a method for preparing a high-efficiency photocatalyst and a method for enhancing Fenton flue gas denitration by using the photocatalyst. Background Art

[0002] With the rapid development of economy, energy demand is rising, the consumption of fossil fuels such as coal, oil and natural gas is increasing year by year, the production capacity of ceramic and non-ferrous metal smelting and processing industry is expanding, and the nitrogen oxides (NO x ) increases sharply, NO x (The main component is NO, accounting for 95%) is one of the main pollutants in the atmosphere, which can form acid rain, haze, photochemical smog, and have serious impacts on human health and the natural environment. At present, flue gas denitrification technology can be divided into two categories: dry and wet. Dry denitrification mainly includes selective catalytic reduction (SCR) technology and selective non-catalytic reduction (SCNR) technology. However, this technology has huge limitations. Since the chemical reaction needs to be carried out at high temperature, for small and medium-sized boilers and industrial boilers, the exhaust temperature is far from the high temperature required for the chemical reaction, and the dust in the flue gas can easily cause the noble metal catalyst in the SCR technology to be poisoned and deactivated, which requires large investment and high maintenance costs. Compared with dry denitrification, wet Fenton denitrification (Fe(II) / H2O2 and Fe(III) / H2O2) has attracted widespread attention due to its simple system, environmental protection, and no secondary pollution. However, in the denitrification process, the rate at which Fe(III) reacts with H2O2 to generate Fe(II) is very slow, resulting in a large amount of Fe(III) accumulation, and Fe(III) is very easy to generate iron oxide precipitation to hinder the reaction.

[0003] Therefore, Fenton denitrification is usually combined with other methods, such as UV-Fenton denitrification. UV light can accelerate the Fe(III) / Fe(II) cycle by converting Fe(III) to Fe(II) through photoreduction, thereby generating more OH to enhance the Fenton denitrification process. However, the effective penetration distance of UV light in the liquid phase is often quite limited. In real-world industrial waste gas, the presence of particulate matter and various impurities is common, resulting in incomplete absorption and utilization of UV light by denitrification absorbents. Therefore, it is necessary to use photocatalysts to enhance the UV effect.

[0004] TiO2 photocatalyst is considered to be the best choice among heterogeneous UV catalysts due to its non-toxicity and wide applicability. Its photocatalytic activity mainly depends on the electron-hole separation ability of the photoinduced catalyst. However, the catalytic ability of existing TiO2 photocatalysts is relatively weak and still cannot meet the application in the field of photocatalytic wet Fenton denitrification technology. It is very necessary to develop high-performance photocatalysts suitable for photocatalytic wet Fenton denitrification. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing an efficient photocatalyst and a method for enhancing Fenton flue gas denitrification using a photocatalyst, so as to solve the problems existing in the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following solutions:

[0007] One of the technical solutions of the present invention is a method for preparing a titanium dioxide photocatalyst with a high (001) crystal face, which uses tetrabutyl titanate (Ti(OC4H9)4) as a Ti source and a hydrofluoric acid (HF) solution as a crystal face regulator to obtain F-TiO2 through a solvent thermal reaction, namely the titanium dioxide photocatalyst with a high (001) crystal face.

[0008] The present invention prepares a high (001) crystal face F-TiO2 photocatalyst by a simple one-step solvothermal method. Compared with synthesis methods such as the sol-gel method and the liquid phase hydrolysis-precipitation method, the present invention has the advantages of simple process and high synthesis efficiency. The reagents used in the preparation process are low in price, and the method is more suitable for promotion and large-scale production.

[0009] Furthermore, the high (001) crystal plane titanium dioxide photocatalyst is a nanosheet structure.

[0010] Furthermore, the preparation method of the titanium dioxide photocatalyst with high (001) crystal plane specifically comprises the following steps:

[0011] Tetrabutyl titanate and hydrofluoric acid solution are mixed to obtain a precursor solution; the precursor solution is heated to perform a solvent thermal reaction to obtain the high (001) crystal plane titanium dioxide photocatalyst.

[0012] Furthermore, the concentration of the hydrofluoric acid solution is 40wt%; the volume ratio of tetrabutyl titanate to the hydrofluoric acid solution is 80:12.8; the temperature of the solvent thermal reaction is 200°C, and the time is 12-24h.

[0013] Furthermore, the preparation method of the titanium dioxide photocatalyst with high (001) crystal plane comprises the following specific steps:

[0014] Under magnetic stirring, 12.8 mL of 40 wt% HF solution was added dropwise to 80 mL of Ti(OC4H9)4 and stirred continuously until the solution was homogeneous to obtain a precursor solution;

[0015] Pour the precursor solution into a 220 mL polytetrafluoroethylene reactor, seal the reactor and place it in an oven for solvothermal reaction at 200° C. for 12-24 h;

[0016] After the solvothermal reaction is completed, the reaction product is cleaned with deionized water and ethanol, dried at 60° C. for 12 h to obtain the high (001) crystal face titanium dioxide photocatalyst (F-TiO2), and ground into powder for collection and storage.

[0017] The second technical solution of the present invention: a titanium dioxide photocatalyst with high (001) crystal surface prepared by the above preparation method.

[0018] The third technical solution of the present invention is a method for preparing a high-efficiency photocatalyst by selectively photodepositing cobalt oxide on high (001) crystal face titanium dioxide, wherein sodium iodate (NaIO3) is used as an electron sacrificial agent, cobalt salt is used as a Co precursor, and the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) is used as a carrier. After being mixed evenly, cobalt oxide selectively loaded on the (001) crystal face of high (001) crystal face titanium dioxide is generated under ultraviolet light conditions to obtain CoO x @F-TiO2 photocatalyst is the highly efficient photocatalyst.

[0019] Furthermore, the method for preparing a high-efficiency photocatalyst by selectively photodepositing cobalt oxide on high (001) crystal face titanium dioxide specifically comprises the following steps:

[0020] The sodium iodate solution, cobalt salt and high (001) crystal face titanium dioxide photocatalyst were mixed evenly, nitrogen was introduced and the mixture was sealed; the sealed mixture system was placed in the dark, stirred for 50 minutes, and then irradiated with ultraviolet light for 1-5 hours to perform a selective photodeposition reaction (a reaction to generate cobalt oxide selectively loaded on the (001) crystal face of high (001) crystal face titanium dioxide) to obtain CoO x @F-TiO2 photocatalyst is the highly efficient photocatalyst.

[0021] Furthermore, the concentration of the sodium iodate solution is 0.1 mol / L; the cobalt salt is CoCl2·2H2O; and the dosage ratio of the sodium iodate solution, the cobalt salt and the high (001) crystal face titanium dioxide photocatalyst is 500 mL: 0.016-0.800 g: 1.0-5.0 g.

[0022] Furthermore, the time for introducing nitrogen is 10 minutes.

[0023] Furthermore, the wavelength of the ultraviolet light irradiation is 254nm and the intensity is 30W.

[0024] Furthermore, the method for preparing a high-efficiency photocatalyst by selectively photodepositing cobalt oxide on high (001) crystal face titanium dioxide comprises the following specific steps:

[0025] 500 mL of 0.1 mol / L NaIO3 solution was placed in a quartz photoreaction bottle, and 0.016-0.800 g of CoCl2·2H2O was added under magnetic stirring. After being evenly mixed, 1.0-5.0 g of the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) was added, and nitrogen was introduced for 10 min while stirring, and the bottle was sealed to maintain anaerobic conditions;

[0026] The sealed mixed system was placed in the dark, kept away from light and stirred for 50 minutes (to allow the ion adsorption on the catalyst surface to reach equilibrium), and then irradiated with 30W 254nm wavelength ultraviolet light for 1-5 hours, while keeping stirring, to carry out a selective photodeposition reaction (a reaction to generate cobalt oxide selectively loaded on the (001) crystal face of titanium dioxide with high (001) crystal face);

[0027] After the selective photodeposition reaction was completed, the mixture was allowed to stand for 30 min, the bottom precipitate was collected, washed with ethanol and deionized water, and dried in vacuum at 60 °C for 10 h to obtain CoO x @F-TiO2 photocatalyst, and grind the dried product into powder for collection and storage.

[0028] Technical solution four of the present invention: a high-efficiency photocatalyst prepared according to the above method.

[0029] Technical solution 5 of the present invention: the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) or the above-mentioned high efficiency photocatalyst (CoO x Application of @F-TiO2) in photocatalytic enhanced Fenton flue gas denitrification.

[0030] Technical solution 6 of the present invention: A method for enhancing Fenton flue gas denitrification using a photocatalyst, comprising the following steps:

[0031] The photocatalyst is dispersed in the Fenton solution, and flue gas containing nitric oxide is introduced to complete flue gas denitrification under ultraviolet light irradiation; the photocatalyst is the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) or the above-mentioned high-efficiency photocatalyst (CoO x @F-TiO2).

[0032] Furthermore, the Fenton solution is a mixed solution of Fe(III) and hydrogen peroxide, the concentration of Fe(III) in the Fenton solution is 5-7mmol / L, and the concentration of hydrogen peroxide is 5-6wt%; the concentration of NO in the flue gas is 500-700ppm, and the concentration of oxygen is 2-4wt%; the dispersed concentration of the photocatalyst in the Fenton solution is 0.05-0.15g / 50mL.

[0033] Further preferably, the concentration of Fe(III) in the Fenton solution is 6 mmol / L, the concentration of hydrogen peroxide is 5.5 wt%; the concentration of NO in the flue gas is 600 ppm, and the concentration of oxygen is 3 wt%; the dispersed concentration of the photocatalyst in the Fenton solution is 0.1 g / 50 mL.

[0034] Furthermore, the pH of the Fenton solution is 3.0 and the temperature is 25° C. (ie, the temperature of the flue gas denitrification reaction is 25° C.).

[0035] Furthermore, the air flow rate of the flue gas is 0.3 L / min.

[0036] Furthermore, the irradiation power of the ultraviolet lamp is 30W, and the irradiation wavelength is 254nm.

[0037] In order to solve the problem of slow Fe(III) / Fe(II) cycle in Fenton flue gas denitrification process, the present invention synthesizes high (001) crystal face titanium dioxide photocatalyst (F-TiO2) and high efficiency photocatalyst (CoO x @F-TiO2), and combined it with Fenton for wet flue gas denitrification. Specifically, the present invention firstly exposes more (001) crystal planes of TiO2 through crystal plane engineering regulation, so that electrons and holes migrate to the (101) and (001) planes respectively, thereby improving the separation efficiency of electrons and holes, and obtaining a high (001) crystal plane titanium dioxide photocatalyst F-TiO2 with improved photocatalytic activity. Then, by selectively photodepositing cobalt oxide on the (001) crystal plane of high (001) crystal plane titanium dioxide, a heterojunction is formed, which further promotes the separation of light-induced charge carriers, increases the catalyst active sites, improves the photocatalytic activity, and obtains a high-efficiency photocatalyst CoO with further improved photocatalytic activity. x @F-TiO2. That is, the present invention prepares titanium dioxide F-TiO2 with a high (001) crystal plane, and then selectively deposits cobalt oxide on the (001) surface of F-TiO2 to synthesize the photocatalyst CoO x @F-TiO2 improves the separation efficiency of photoinduced carriers and enhances its UV catalytic Fenton activity. This strategy can effectively solve the problem of slow Fe(III) / Fe(II) cycle in Fenton wet denitrification.

[0038] The present invention discloses the following technical effects:

[0039] (1) The present invention achieves crystal plane separation by regulating TiO2 photocatalyst through fluorination, and selectively increases the proportion of (001) crystal plane, promotes the separation and transfer of photogenerated electrons and holes, and enhances the photocatalytic activity, thereby obtaining a high (001) crystal plane titanium dioxide photocatalyst F-TiO2 with improved photocatalytic activity.

[0040] (2) The present invention selectively deposits cobalt oxide on the (001) crystal plane of titanium dioxide with a high (001) crystal plane to form a heterojunction, further realizing the separation of electrons and holes, increasing the catalyst active sites, and improving the photocatalytic activity, thereby obtaining a highly efficient photocatalyst CoO with further improved photocatalytic activity. x @F-TiO2.

[0041] (3) The present invention provides a method for enhancing Fenton denitrification using a photocatalyst, wherein the photocatalyst is F-TiO2 or CoO x @F-TiO2 can accelerate the Fe(III) / Fe(II) cycle, improve the Fenton efficiency, and enhance the NO capture capacity to achieve efficient denitrification. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0043] Figure 1 For the preparation of CoO in Example 2 of the present invention x @Schematic diagram of the F-TiO2 photocatalyst and the synthetic route for preparing the F-TiO2 photocatalyst in Example 1;

[0044] Figure 2 CoO prepared in Example 2 x @F-TiO2 photocatalyst morphology characterization test results, where (a) is the SEM image, (b) is the HR-TEM image, (c) and (d) are EDS images;

[0045] Figure 3 CoO prepared in Example 2 x @X-ray diffraction pattern (a) and Raman spectrum (b) of F-TiO2 photocatalyst, F-TiO2 photocatalyst prepared in Example 1 and TiO2 photocatalyst prepared in Comparative Example 1;

[0046] Figure 4 CoO prepared in Example 2 x @XPS full spectrum of F-TiO2 photocatalyst and F-TiO2 photocatalyst prepared in Example 1;

[0047] Figure 5 CoO prepared in Example 2 x@Comparison graph of photocurrent response (a), photoluminescence spectrum (b) and AC impedance (c) of F-TiO2 photocatalyst, F-TiO2 photocatalyst prepared in Example 1 and TiO2 photocatalyst prepared in Comparative Example 1;

[0048] Figure 6 This is the process equipment diagram used in the flue gas denitrification experiment, where 1-NO cylinder; 2-N2 (or Ar) cylinder; 3-O2 cylinder; 4-gas valve; 5-mass flowmeter; 6-gas mixing tank; 7-glass rotor flowmeter; 8-reaction bottle; 9-ultraviolet lamp; 10-water bath; 11-tail gas absorption device; 12-flue gas analyzer;

[0049] Figure 7 Fe(III)+H2O2, UV+Fe(III)+H2O2, UV+TiO2 photocatalyst prepared in comparative example 1+Fe(III)+H2O2, UV+F-TiO2 photocatalyst prepared in example 1+Fe(III)+H2O2, UV+CoO2 prepared in example 2 x @Denitrification effect under five modes of F-TiO2 photocatalyst + Fe(III) + H2O2. DETAILED DESCRIPTION

[0050] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0051] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0052] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0053] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0054] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0055] The present invention provides a method for preparing a titanium dioxide photocatalyst with a high (001) crystal face, wherein tetrabutyl titanate (Ti(OC4H9)4) is used as a Ti source, and a hydrofluoric acid (HF) solution is used as a crystal face regulator, and a solvent thermal reaction is performed to obtain F-TiO2, which is the titanium dioxide photocatalyst with a high (001) crystal face. The preparation method modifies the photocatalyst TiO2 by fluorination, changes the crystal structure of the TiO2 photocatalyst to anatase type, regulates the photocatalyst crystal face type to coexist with (001) crystal face and (010) crystal face, and controls the (001) crystal face to account for about 80%. These means are used to promote the separation and transfer of photogenerated electrons and holes, enhance the photocatalytic activity, and improve the iron cycle efficiency in the Fenton process, thereby enhancing the Fenton denitrification effect.

[0056] The present invention prepares a high (001) crystal face F-TiO2 photocatalyst by a simple one-step solvothermal method. Compared with synthesis methods such as the sol-gel method and the liquid phase hydrolysis-precipitation method, the present invention has the advantages of simple process and high synthesis efficiency. The reagents used in the preparation process are low in price, and the method is more suitable for promotion and large-scale production.

[0057] As a specific embodiment of the present invention, the preparation method of the high (001) crystal plane titanium dioxide photocatalyst specifically comprises the following steps:

[0058] Tetrabutyl titanate and hydrofluoric acid solution are mixed to obtain a precursor solution; the precursor solution is heated to perform a solvent thermal reaction to obtain the high (001) crystal plane titanium dioxide photocatalyst.

[0059] As a preferred embodiment of the present invention, the concentration of the hydrofluoric acid solution is 40wt%; the volume ratio of the tetrabutyl titanate to the hydrofluoric acid solution is 80:12.8.

[0060] As a preferred embodiment of the present invention, the temperature of the solvent thermal reaction is 200°C and the time is 12-24h. The reaction temperature plays a key role in controlling the thickness and size of the TiO2 nanosheets. When the reaction temperature is too high, the TiO2 nanosheets become larger and slightly thicker. When the reaction temperature is too low, the TiO2 nanosheets are small and thin, resulting in insufficient exposure of the (001) crystal plane, which will reduce the photocatalytic performance. The optimal reaction condition for obtaining the maximum (001) crystal plane percentage is 200°C, and the (001) crystal plane of the prepared nanosheet accounts for 80%.

[0061] As a preferred embodiment of the present invention, the preparation method of the titanium dioxide photocatalyst with high (001) crystal surface comprises the following specific steps:

[0062] Under magnetic stirring, 12.8 mL of 40 wt% HF solution was added dropwise to 80 mL of Ti(OC4H9)4 and stirred continuously until the solution was homogeneous to obtain a precursor solution;

[0063] Pour the precursor solution into a 220 mL polytetrafluoroethylene reactor, seal the reactor and place it in an oven for solvothermal reaction at 200° C. for 12-24 h;

[0064] After the solvothermal reaction is completed, the reaction product is cleaned with deionized water and ethanol, dried at 60° C. for 12 h to obtain the high (001) crystal face titanium dioxide photocatalyst (F-TiO2), and ground into powder for collection and storage.

[0065] The present invention also provides a titanium dioxide photocatalyst with a high (001) crystal surface prepared by the above preparation method.

[0066] The present invention also provides a method for preparing a high-efficiency photocatalyst by selectively photodepositing cobalt oxide on titanium dioxide with a high (001) crystal face, wherein sodium iodate (NaIO3) is used as an electron sacrificial agent, a cobalt salt is used as a Co precursor, and the above-mentioned titanium dioxide photocatalyst with a high (001) crystal face (F-TiO2) is used as a carrier. After being uniformly mixed, cobalt oxide selectively loaded on the (001) crystal face of titanium dioxide with a high (001) crystal face is generated under ultraviolet light conditions to obtain CoO x @F-TiO2 photocatalyst is the highly efficient photocatalyst.

[0067] As a specific embodiment of the present invention, the method for preparing a high-efficiency photocatalyst by selectively photodepositing cobalt oxide on high (001) crystal face titanium dioxide specifically comprises the following steps:

[0068] The sodium iodate solution, cobalt salt and high (001) crystal face titanium dioxide photocatalyst were mixed evenly, nitrogen was introduced and the mixture was sealed; the sealed mixture system was placed in the dark, stirred for 50 minutes, and then irradiated with ultraviolet light for 1-5 hours to perform a selective photodeposition reaction (a reaction to generate cobalt oxide selectively loaded on the (001) crystal face of high (001) crystal face titanium dioxide) to obtain CoO x @F-TiO2 photocatalyst is the highly efficient photocatalyst.

[0069] The cobalt oxide loaded on the (001) crystal plane takes advantage of the high entropy function of the cobalt element, which has good catalytic performance. At the same time, the introduction of cobalt oxide will form a heterojunction on the (001) crystal plane, and the photogenerated holes can further gather near the cobalt oxide, improving the catalytic performance of the active sites, while improving the separation performance of photogenerated electrons and holes, and inhibiting the recombination of electrons and holes.

[0070] As a preferred embodiment of the present invention, the concentration of the sodium iodate solution is 0.1 mol / L; the cobalt salt is CoCl2·2H2O; the dosage ratio of the sodium iodate solution, the cobalt salt and the high (001) crystal surface titanium dioxide photocatalyst is 500mL:0.016-0.800g:1.0-5.0g.

[0071] As a preferred embodiment of the present invention, the time for introducing nitrogen is 10 minutes.

[0072] As a preferred embodiment of the present invention, the wavelength of the ultraviolet light irradiation is 254nm and the intensity is 30W.

[0073] As a preferred embodiment of the present invention, the method for preparing a high-efficiency photocatalyst by selectively photodepositing cobalt oxide on high (001) crystal face titanium dioxide comprises the following specific steps:

[0074] 500 mL of 0.1 mol / L NaIO3 solution was placed in a quartz photoreaction bottle, and 0.016-0.800 g of CoCl2·2H2O was added under magnetic stirring. After being evenly mixed, 1.0-5.0 g of the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) was added, and nitrogen was introduced for 10 min while stirring, and the bottle was sealed to maintain anaerobic conditions;

[0075] The sealed mixed system was placed in the dark, kept away from light and stirred for 50 minutes (to allow the ion adsorption on the catalyst surface to reach equilibrium), and then irradiated with 30W 254nm wavelength ultraviolet light for 1-5 hours, while keeping stirring, to carry out a selective photodeposition reaction (a reaction to generate cobalt oxide selectively loaded on the (001) crystal face of titanium dioxide with high (001) crystal face);

[0076] After the selective photodeposition reaction was completed, the mixture was allowed to stand for 30 min, the bottom precipitate was collected, washed with ethanol and deionized water, and dried in vacuum at 60 °C for 10 h to obtain CoO x @F-TiO2 photocatalyst, and grind the dried product into powder for collection and storage.

[0077] The present invention also provides a high-efficiency photocatalyst prepared according to the method.

[0078] The present invention also provides the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) or the above-mentioned high efficiency photocatalyst (CoO x Application of @F-TiO2) in photocatalytic enhanced Fenton flue gas denitrification.

[0079] The present invention also provides a method for enhancing Fenton flue gas denitrification using a photocatalyst, comprising the following steps:

[0080] The photocatalyst is dispersed in the Fenton solution, and flue gas containing nitric oxide is introduced to complete flue gas denitrification under ultraviolet light irradiation; the photocatalyst is the above-mentioned high (001) crystal face titanium dioxide photocatalyst (F-TiO2) or the above-mentioned high-efficiency photocatalyst (CoO x @F-TiO2).

[0081] As a preferred embodiment of the present invention, the Fenton solution is a mixed solution of Fe(III) and hydrogen peroxide, the concentration of Fe(III) in the Fenton solution is 5-7mmol / L, and the concentration of hydrogen peroxide is 5-6wt%; the concentration of NO in the flue gas is 500-700ppm, and the concentration of oxygen is 2-4wt%; the dispersed concentration of the photocatalyst in the Fenton solution is 0.05-0.15g / 50mL.

[0082] As a more preferred embodiment of the present invention, the concentration of Fe(III) in the Fenton solution is 6 mmol / L, and the concentration of hydrogen peroxide is 5.5 wt%; the concentration of NO in the flue gas is 600 ppm, and the concentration of oxygen is 3 wt%; the dispersed concentration of the photocatalyst in the Fenton solution is 0.1 g / 50 mL.

[0083] As a preferred embodiment of the present invention, the pH of the Fenton solution is 3.0 and the temperature is 25° C. (ie, the temperature of the flue gas denitration reaction is 25° C.).

[0084] As a preferred embodiment of the present invention, the air flow rate of the flue gas is 0.3 L / min.

[0085] As a preferred embodiment of the present invention, the irradiation power of the ultraviolet lamp is 30W, and the irradiation wavelength is 254nm.

[0086] The technical solution of the present invention is further described below through specific embodiments.

[0087] The experimental methods used in the specific embodiments of the present invention are conventional methods unless otherwise specified. The materials, reagents and instruments used are conventional materials, reagents and instruments in the art unless otherwise specified, and can be purchased by those skilled in the art through commercial channels.

[0088] Example 1

[0089] A preparation method of a titanium dioxide photocatalyst with high (001) crystal surface (F-TiO2) is as follows (synthesis route schematic diagram as shown in Figure 1 shown):

[0090] Under magnetic stirring, 12.8 mL of 40 wt% HF solution was added dropwise to 80 mL of Ti(OC4H9)4 and stirred continuously until the solution was uniform (stirring time was 15 min) to obtain a precursor solution;

[0091] The precursor solution was poured into a 220 mL polytetrafluoroethylene reactor, which was sealed and placed in an oven for solvothermal reaction at 200 °C for 24 h;

[0092] After the solvothermal reaction, the reaction product was cleaned with deionized water and ethanol, dried at 60°C for 12 h to obtain a high (001) crystal face titanium dioxide photocatalyst (F-TiO2), which was ground into powder and collected for storage.

[0093] Comparative Example 1

[0094] Preparation of ordinary TiO2:

[0095] The same as Example 1, except that the amount of 40wt% HF solution is 0mL, that is, TiO2 is not modified with fluorine. The specific preparation method is as follows:

[0096] Under magnetic stirring, 12.8 mL of deionized water was added dropwise to 80 mL of Ti(OC4H9)4 and stirred continuously until the solution was uniform to obtain a precursor solution;

[0097] The precursor solution was poured into a 220 mL polytetrafluoroethylene reactor, which was sealed and placed in an oven for solvothermal reaction at 200 °C for 24 h;

[0098] After the solvothermal reaction was completed, the reaction product was cleaned with deionized water and ethanol, dried at 60°C for 12 h to obtain a TiO2 photocatalyst, which was then ground into powder and collected and stored.

[0099] Example 2

[0100] Highly efficient photocatalyst (CoO x@F-TiO2) preparation, the steps are as follows (synthesis route schematic diagram as shown Figure 1 shown):

[0101] 500 mL of 0.1 mol / L NaIO3 solution was placed in a quartz photoreaction bottle, and 0.016 g of CoCl2·2H2O was added under magnetic stirring. After mixing evenly, 2.0 g of F-TiO2 prepared in Example 1 was added, and nitrogen was introduced for 10 min while stirring. The bottle was sealed to maintain anaerobic conditions.

[0102] The sealed mixed system was placed in the dark and stirred for 50 minutes in the dark to allow the ion adsorption on the F-TiO2 surface to reach equilibrium, and then irradiated with 30W 254nm wavelength ultraviolet light for 3 hours while stirring to carry out a selective photodeposition reaction (a reaction to generate cobalt oxide selectively loaded on the (001) crystal face of titanium dioxide with high (001) crystal face);

[0103] After the selective photodeposition reaction was completed, the mixture was allowed to stand for 30 min, the bottom precipitate was collected, washed with ethanol and deionized water, and dried in vacuum at 60 °C for 10 h to obtain CoO x @F-TiO2 photocatalyst, and grind the dried product into powder for collection and storage.

[0104] Performance Testing

[0105] 1. Catalyst characterization test

[0106] 1. Morphology characterization

[0107] Figure 2 CoO prepared in Example 2 x @F-TiO2 photocatalyst morphology characterization test results, first, the CoO prepared in Example 2 x @F-TiO2 was tested by SEM, SEM image ( Figure 2 (a) shows that the synthesized catalyst is a truncated octahedral structure with a diameter of about 100 nm and a thickness of about 10 nm. Then it was tested by TEM, and the high-resolution TEM (HR-TEM) image ( Figure 2 (b) directly shows that the lattice spacing parallel to the top and bottom facets is about 0.232nm, corresponding to the (001) plane of anatase TiO2. x @F-TiO2 has a (001) crystal plane of about 80%. In addition, EDS mapping was used to investigate the CoO x @Element composition and distribution of F-TiO2 photocatalyst, EDS image ( Figure 2(c), (d)) show that the samples have Ti, Co, O, and F signals, indicating that cobalt oxide has been successfully loaded on the TiO2 surface. Moreover, as shown in Figures (c) and (d), the Co element bright spots are not evenly distributed on the surface of the TiO2 nanosheets, but are clearly sparse and dense, and are mostly distributed in a linear manner, which indirectly indicates that cobalt oxide has a tendency to selectively deposit on the (001) crystal plane of the TiO2 nanosheets.

[0108] 2. Crystal structure

[0109] The CoO prepared in Example 2 x @F-TiO2, F-TiO2 prepared in Example 1 and TiO2 prepared in Comparative Example 1 were subjected to XRD and Raman tests. The results are as follows Figure 3 As shown in the figure, (a) is the XRD image and (b) is the Raman image. As shown in the XRD image, strong diffraction peaks 2θ appear at 25.29°, 37.81°, 40.05°, 53.89°, 55.06° and 62.69°, respectively, corresponding to the (101), (004), (200), (105), (211) and (204) crystal planes of tetragonal anatase TiO2 (JCPDS No.21-1272). In addition, compared with pure TiO2, F-TiO2 and CoO x The intensity of the (004) diffraction peak of F-TiO2 decreases, and its half-peak width becomes wider, which indicates that the thickness of the TiO2 nanosheets in the (001) crystal axis direction decreases; in addition, the intensity of the (200) peak of both increases, and its half-peak width becomes narrower, which indicates that the side length of the TiO2 nanosheets in the (100) crystal axis direction increases. Therefore, according to the characterization results of XRD, it can be seen that F-TiO2 and CoO x @F-TiO2 can expose more (001) crystal planes. From the Raman image (Raman spectrum), we can see that compared with pure TiO2, F-TiO2 and CoO x @144 and 636cm of F-TiO2 -1 E g The intensity of the peak decreased, while the 394 cm -1 B 1g Peak and 514cm -1 A 1g The intensity of the peak increases, and the higher the percentage of (001) crystal plane exposure, the higher the E g The intensity of the peak decreases, A 1g and B 1g The intensity of the peak increases. Therefore, the Raman spectrum results further illustrate that F-TiO2 and CoO x @F-TiO2 is rich in a high proportion of (001) crystal planes.

[0110] 3. Surface characteristics

[0111] XPS analysis of CoO prepared in Example 2 x The surface electronic states of F-TiO2 and F-TiO2 prepared in Example 1 are as follows Figure 4 shown. Figure 4 The peaks at 779.9 eV and 796.5 eV belong to Co 2p 3 / 2 and Co 2p 1 / 2 Characteristic peak. The spin-orbit splitting value of Co2p is 16.6 eV, indicating that the valence of the Co element in the photocatalyst is +2 or +3, and the selectively deposited cobalt oxide can be labeled as CoO x The characteristic peaks at 458.08 eV and 463.96 eV correspond to CoO x Ti 2p in @F-TiO2 structure 3 / 2 and Ti 2p 1 / 2 , which is a typical Ti-O peak in TiO2; and compared with the undeposited F-TiO2, CoO x @F-TiO2Ti 2p peak shifts to the high binding energy region, attributed to CoO x @F-TiO2 TiO2 and CoO in the preparation process x The peaks at 529.1eV and 529.5eV are related to lattice oxygen (Co-O) and -OH (Co-OH) adsorbed on the surface, respectively.

[0112] 4. Photoelectric performance test

[0113] The CoO prepared in Example 2 was tested using an electrochemical workstation. x @The photocurrent responses of F-TiO2, F-TiO2 prepared in Example 1 and TiO2 prepared in Comparative Example 1 are as follows Figure 5 As shown in (a), it can be seen that compared with pure TiO2 and high (001) crystal plane F-TiO2 constructed by crystal plane engineering, CoO x @F-TiO2 has a higher photocurrent density and can show better electron-hole separation efficiency; the CoO prepared in Example 2 was tested by a fluorescence spectrophotometer. x @The photoluminescence (PL) properties of F-TiO2, F-TiO2 prepared in Example 1 and TiO2 prepared in Comparative Example 1 are shown in the following table. Figure 5 As shown in (b), it can be seen that CoO x The PL emission intensity of @F-TiO2 is much weaker than that of F-TiO2 and TiO2, indicating that the crystal surface engineering design and surface heterostructure structure can effectively suppress the recombination of photoinduced electrons and holes; the CoO prepared in Example 2 was tested by an electrochemical workstation. x@EIS of F-TiO2, F-TiO2 prepared in Example 1 and TiO2 prepared in Comparative Example 1. The results are as follows Figure 5 As shown in (c), it can be seen that compared with pure TiO2 and high (001) crystal plane F-TiO2 constructed by crystal plane engineering, CoO x @F-TiO2 catalyst surface has a higher electron migration rate and can show better hole-electron separation efficiency.

[0114] 2. Flue gas denitrification experiment

[0115] The equipment process diagram for the flue gas denitrification experiment is shown in Figure 6 , among which, 1-NO cylinder; 2-N2 (or Ar) cylinder; 3-air cylinder; 4-gas valve; 5-mass flowmeter; 6-gas mixing tank; 7-glass rotor flowmeter; 8-reaction bottle; 9-ultraviolet lamp; 10-water bath; 11-tail gas absorption device; 12-flue gas analyzer. The absorption device mainly includes three parts: waste simulation device, photocatalytic reactor and gas absorption detection device. The gas device includes N2 (or Ar), air and NO gas cylinders; the photocatalytic reactor is mainly composed of a 500mL quartz absorption bottle, which is immersed in a water bath, and a fully submersible ultraviolet lamp is deeply inserted into the quartz bottle. The temperature of the whole system is controlled by a water bath. The gas detection device is mainly a flue gas analyzer testo 330-2.

[0116] (1) UV (ultraviolet) + CoO prepared in Example 2 x @F-TiO2 photocatalyst+Fe(III)+H2O2

[0117] First, 208 mL of deionized water and 0.725 g of ammonium ferric sulfate dodecahydrate (NH4Fe(SO4)2·12H2O) were added to a quartz reaction bottle to obtain a Fe(III) solution. Then, 0.5 g of CoO prepared in Example 2 was added under magnetic stirring. x@F-TiO2 photocatalyst, evenly dispersed. Then, simulated flue gas was introduced, the air flow rate of the simulated flue gas was 0.3L / min, the NO concentration in the simulated flue gas was 500ppm, and air was introduced to mix with NO (i.e., air was used as the balance gas), and a mixed gas with an O2 concentration of 3wt% and a NO concentration of 500ppm was prepared as simulated flue gas (by adjusting the ratio of NO and air flow rates, simulated flue gas with different concentrations of NO and O2 was obtained. If you want to compare the reaction under anaerobic conditions, N2 (or Ar) is introduced to create an anaerobic environment). At the beginning of the reaction, 42 mL of 30 wt% H2O2 (208 mL of deionized water + 0.725 g of ammonium ferric sulfate dodecahydrate + 42 mL of 30 wt% H2O2 constitutes a Fenton solution, and the pH of the Fenton solution is adjusted to 3.0) is added to the Fe(III) solution, and the quartz reaction bottle is immersed in a 25°C water bath, and a fully submersible ultraviolet lamp is inserted into the quartz glass reaction bottle and turned on (wavelength 254 nm, power 30 W), and the temperature of the entire system is controlled by a water bath (±0.1°C). The NO concentration in the outlet gas is measured with a flue gas analyzer every 3 minutes, and the NO removal efficiency η is calculated according to formula (1).

[0118]

[0119] Where η is the removal efficiency of NO, %, C in is the inlet concentration of NO, ppm; C out is the NO outlet concentration, ppm.

[0120] CoO x @F-TiO2 photocatalyst enhances the denitrification effect of photo-Fenton denitrification Figure 7 .

[0121] (2) UV + F-TiO2 photocatalyst prepared in Example 1 + Fe(III) + H2O2

[0122] The experimental process is the same as (1), except that 0.5 g of CoO prepared in Example 2 is added x @F-TiO2 photocatalyst was replaced with 0.5 g of F-TiO2 photocatalyst prepared in Example 1.

[0123] The denitrification effect of F-TiO2 photocatalyst enhanced Fenton denitrification is shown in Figure 7 .

[0124] (3) UV + TiO2 photocatalyst prepared in Comparative Example 1 + Fe(III) + H2O2

[0125] The experimental process is the same as (1), except that 0.5 g of CoO prepared in Example 2 is added x@F-TiO2 photocatalyst was replaced with 0.5 g of TiO2 photocatalyst prepared in Comparative Example 1.

[0126] The denitrification effect of TiO2 photocatalyst enhanced Fenton denitrification is shown in Figure 7 .

[0127] (4) UV+Fe(III)+H2O2

[0128] The experimental process is the same as (1), the only difference is that no photocatalyst is added.

[0129] The denitrification effect of photo-Fenton denitrification is shown in Figure 7 .

[0130] (5)Fe(III)+H2O2

[0131] The experimental process is the same as (1), except that no photocatalyst is added and no UV irradiation is performed.

[0132] The denitrification effect of Fenton denitrification is shown in Figure 7 .

[0133] Depend on Figure 7 It can be seen that Fe(III)+H2O2, UV+Fe(III)+H2O2, UV+TiO2 photocatalyst prepared in Comparative Example 1+Fe(III)+H2O2, UV+F-TiO2 photocatalyst prepared in Example 1+Fe(III)+H2O2, UV+CoO2 prepared in Example 2 x @F-TiO2 photocatalyst + Fe(III) + H2O2, the absorption rates of NO after 30 min were 48.71%, 56.1%, 60.40%, 75.79% and 81.23% respectively. This result proves that the introduction of ultraviolet light can greatly improve the Fenton denitrification effect. In addition, the addition of photocatalyst can further improve the denitrification effect of Fe(III) / H2O2 photo-Fenton. x @F-TiO2 photocatalyst has the best effect, therefore, CoO x @F-TiO2 photocatalyst can be used as a photocatalyst with good Fenton denitrification effect.

[0134] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a titanium dioxide photocatalyst with a high (001) crystal plane, characterized in that: Tetrabutyl titanate is used as a Ti source and a hydrofluoric acid solution is used as a crystal surface regulator. Through a solvent thermal reaction, F-TiO2 is obtained, which is the high (001) crystal surface titanium dioxide photocatalyst.

2. The method for preparing a titanium dioxide photocatalyst with a high (001) crystal plane according to claim 1, characterized in that: The concentration of the hydrofluoric acid solution is 40wt%; the volume ratio of tetrabutyl titanate to the hydrofluoric acid solution is 80:12.8; the temperature of the solvent thermal reaction is 200°C and the time is 12-24h.

3. A titanium dioxide photocatalyst with a high (001) crystal surface obtained by the preparation method according to any one of claims 1 to 2.

4. A method for preparing a high-efficiency photocatalyst by selective photodeposition of cobalt oxide on high (001) crystal face titanium dioxide, characterized in that: Sodium iodate is used as an electron sacrificial agent, cobalt salt is used as a Co precursor, and the high (001) crystal face titanium dioxide photocatalyst according to claim 3 is used as a carrier. After being evenly mixed, cobalt oxide selectively loaded on the (001) crystal face of the high (001) crystal face titanium dioxide is generated under ultraviolet light conditions to obtain CoO x @F-TiO2 photocatalyst is the highly efficient photocatalyst.

5. The method for preparing a high-efficiency photocatalyst by selective photodeposition of cobalt oxide on high (001) crystal plane titanium dioxide according to claim 4, characterized in that: The specific steps include: The sodium iodate solution, cobalt salt and high (001) crystal face titanium dioxide photocatalyst were mixed evenly, nitrogen was introduced and sealed; the sealed mixed system was placed in the dark, stirred for 50 minutes, and then irradiated with ultraviolet light for 1-5 hours to perform selective photodeposition reaction to obtain CoO x @F-TiO2 photocatalyst is the highly efficient photocatalyst.

6. The method for preparing a high-efficiency photocatalyst by selective photodeposition of cobalt oxide on high (001) crystal face titanium dioxide as claimed in claim 5, characterized in that: The concentration of the sodium iodate solution is 0.1 mol / L; the cobalt salt is CoCl2·2H2O; the dosage ratio of the sodium iodate solution, the cobalt salt and the high (001) crystal surface titanium dioxide photocatalyst is 500mL:0.016-0.800g:2.00g, and the dosage of the cobalt salt is not 0.

7. A high-efficiency photocatalyst prepared according to the method according to any one of claims 4 to 6.

8. Use of the high (001) crystal face titanium dioxide photocatalyst according to claim 3 or the high-efficiency photocatalyst according to claim 7 in photocatalytically enhanced Fenton flue gas denitrification.

9. A method for enhancing Fenton flue gas denitrification using a photocatalyst, characterized in that: The following steps are involved: The photocatalyst is dispersed in a Fenton solution, and flue gas containing nitric oxide is introduced to complete flue gas denitrification under ultraviolet light irradiation; the photocatalyst is the high (001) crystal face titanium dioxide photocatalyst described in claim 3 or the high-efficiency photocatalyst described in claim 7.

10. The method according to claim 9, characterized in that The Fenton solution is a mixed solution of Fe(III) and hydrogen peroxide, wherein the concentration of Fe(III) in the Fenton solution is 5-7 mmol / L, and the concentration of hydrogen peroxide is 5-6 wt %; the concentration of NO in the flue gas is 500-700 ppm, and the concentration of oxygen is 2-4 wt %; and the dispersed concentration of the photocatalyst in the Fenton solution is 0.05-0.15 g / 50 mL.

Citation Information

Patent Citations

  • Photocatalytic water oxidation catalyst and preparation method thereof

    CN108325529A

  • Z-system visible light catalytic material based on crystal surface energy level difference and hole trap synergy effects and preparation method thereof

    CN110586130A

  • Cobalt oxide nano-particle loaded sodium bismuth titanate piezoelectric catalyst as well as preparation method and application thereof

    CN116426966A

  • Fluorine-titanium dioxide photocatalysis and Fe (II) EDTA (Ethylene Diamine Tetraacetic Acid) synergistic denitration method

    CN116726959A

  • Topical formulation of hyperbranched polymer-coated particles

    US20180256480A1